Learning motivation and time concept of learners from low socio-economic environments - Grobler, Rina (Acta Academica: Critical views on society, culture and politics, 2009)
Due to an unsatisfactory learner performance in many schools in South Africa a need was identified to explore some of the factors that might influence learner performance. The objective of this investigation was first to study school learners’ concept of time, coupled with their learning motivation, in secondary schools located in low socio-economic environments in Gauteng and, secondly, to investigate whether there were differences between the perceptions of learners in schools located in both informal and formal housing environments.